Critical Thinking Skiils and Students' Achievement on Biology Lesson using Genetic Instructional Material based on Learning Cycle 5E: A Correlational Study - Muhammad Shobirin; AD. Corebima; Betty Lukiati (Jurnal Pendidikan Sains, 2019)
Abstract: The aim of this research is to uncover correlation between critical thinking skills and student achievement and the contributions of critical thinking skills on student achievement through learning Biology using genetic teaching material that developed based on learning cycle 5E model. This research used correlational design. The population of this research was all of student grade XII-IPA at state senior high school. The sample were student of class XII-IPA3 that consist of 30 students. The result showed that there is correlation between critical thinking skills and student achievement in Biology learning using genetic teaching material that developed based on learning cycle 5E model with the regression equation Y = 0,511X–35,271. Based on the value R square analysis showed that critical thinking skills gives contribution 55,2% on student achievement.Key Words: critical thinking skills, student achievement, learning cycle 5E, genetic teaching materialsAbstrak: Penelitian ini bertujuan untuk mengetahui hubungan keterampilan berpikir kritis dengan hasil belajar siswa SMA serta sumbangan keterampilan berpikir kritis terhadap hasil belajar dalam pembelajaran Biologi menggunakan bahan ajar genetika berbasis learning cycle 5E. Rancangan penelitian yang digunakan adalah penelitian korelasional. Populasi adalah seluruh siswa kelas XII IPA di SMA Negeri. Sampel adalah siswa kelas XII IPA 3 yang terdiri dari 30 siswa. Hasil penelitian menunjukkan bahwa ada hubungan antara keterampilan berpikir kritis dengan hasil belajar siswa pada pembelajaran Biologi menggunakan bahan ajar genetika berbasis learning cycle 5E dengan persamaan regresi hubungan kedua variabel adalah Y = 0,511X – 35,271. Berdasarkan nilai R2 diketahui sumbangan keterampilan berpikir kritis terhadap hasil belajar siswa sebesar 55,2%.Kata kunci: keterampilan berpikir kritis, hasil belajar, learning cycle 5E, bahan ajar genetika